(untitled) (Applied Biological Research, 2023)
Cardiovascular diseases (CVD) are a cluster of diseases that hamper cardio vascular system and may lead to death. Several injuries and risk factors like obesity correspond to the malfunctioning of heart and blood vessels that lead to the condition of stroke, myocardial infarction, deep vein thrombosis (DVT), etc. Only a few studies have depicted the role of mitochondrial genes and their epigenetic regulation in DVT. The association of certain mitochondrial genes of electron transport chain and oxidative phosphorylation has been reported in Expression of these genes is regulated by DNA methylation. Obesity not only influences the CVD but also has been found responsible for alteration in mtDNA methylation. In present study, of the 5182 research articles, only 13 and 4 papers were found dealing with the qualitative and quantitative analysis, respectively. MT-CO1, MT-CO2, MT-CO3, MT-TL1 and PPARGC1 genes were noted to be involved in disease condition. The mitochondrial DNA methylation has profound impact on mitochondrial gene expression which may lead to the development of dysfunctional mitochondria and cause the development of various cardiovascular diseases. In present paper, a systemic analysis was done with the hypothesis that mitochondrial DNA methylation has an intriguing role in the occurrence of several CVDs in relation to obesity.